2021
DOI: 10.3390/ijms23010115
|View full text |Cite
|
Sign up to set email alerts
|

chi-miR-487b-3p Inhibits Goat Myoblast Proliferation and Differentiation by Targeting IRS1 through the IRS1/PI3K/Akt Signaling Pathway

Abstract: MicroRNAs (miRNAs) are endogenously expressed small noncoding RNAs and play critical roles in the regulation of post-transcriptional gene expression. Our previous study uncovered that chi-miR-487b-3p is widespread in different goat tissues, which is significantly higher in muscle, especially in lamb. Here, we demonstrate the role of chi-miR-487b-3p as a myogenic miRNA that regulates skeletal muscle development. chi-miR-487b-3p overexpression was demonstrated to significantly inhibit goat myoblast proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
(54 reference statements)
0
15
0
Order By: Relevance
“…Meanwhile, si-circ_003628 increased the expression level of p27 . It has been reported that Pax7 , CDK2 , CDK4 and CyclinD1 in expression promoted the proliferation of goat SMSCs, while p27 inhibited the proliferation of goat SMSCs [ 27 , 46 ]. This taken together with the inhibited effect of si-circ_003628 on goat SMSCs, suggests that circ_003628 promotes proliferation of goat SMSCs by regulating the expression of the proliferation marker genes, eventually leading to the hypertrophy of muscle fibers and increase of skeletal muscle mass in goats.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, si-circ_003628 increased the expression level of p27 . It has been reported that Pax7 , CDK2 , CDK4 and CyclinD1 in expression promoted the proliferation of goat SMSCs, while p27 inhibited the proliferation of goat SMSCs [ 27 , 46 ]. This taken together with the inhibited effect of si-circ_003628 on goat SMSCs, suggests that circ_003628 promotes proliferation of goat SMSCs by regulating the expression of the proliferation marker genes, eventually leading to the hypertrophy of muscle fibers and increase of skeletal muscle mass in goats.…”
Section: Discussionmentioning
confidence: 99%
“…During reproduction, regulating cell cycle-related factors contributes to better follicle development and protects female fertility ( 30 , 31 ). Activation of the PI3K-Akt signaling pathway and Oocyte meiosis can promote oocyte maturation ( 32 34 ). Our results suggest that the cell cycle, PI3K-Akt signaling pathway, and Oocyte meiosis play important roles in follicle development.…”
Section: Discussionmentioning
confidence: 99%
“…Glyceraldehyde 3-phosphate dehydrogenase was used as an endogenous control gene for mRNA, and U6 for miRNA. Relative quantitative levels were calculated based on the 2 −ΔΔCt method [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…The formation of animal muscle tissue mainly depends upon the accumulation of proteins and the coordination of muscle cell proliferation, differentiation, and apoptosis, and includes three main stages: myotube formation, myotube differentiation into muscle fibers, and muscle fiber growth and maturation [ 1 ]. Skeletal muscle satellite cells (SMSCs) have stem-cell-like properties and are involved in postnatal skeletal muscle regeneration and growth [ 2 , 3 , 4 ]. Due to their myogenic and adipogenic differentiation capacity, SMSCs have become a suitable model for investigating postnatal muscle growth and intramuscular adipogenesis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation